1999
DOI: 10.1021/ja983984p
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition between Genetically Engineered Streptavidin and Surface-Bound Biotin

Abstract: This study examines the binding of wild-type streptavidin and streptavidin mutants to biotinterminated self-assembled monolayers (SAMs) as a model of biomolecular recognition at solid-liquid interfaces. The types of streptavidin proteins employed in this work were wild-type, Tyr43Ala (Y43A), and Trp120Ala (W120A), which have biotin-binding affinities that span several orders of magnitude (K a varies from ∼10 13 M -1 for wild-type to 10 7 M -1 for W120A). Two types of biotin-terminated monolayers were examined:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
200
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(227 citation statements)
references
References 33 publications
25
200
2
Order By: Relevance
“…The reason was that the ureido-and tetrahydrothiophene-rings of biotin are more hydrophilic than −NH 2 terminated cysteamine SAM [26]. The contact angle of biotin SAM was smaller than the previously reported one in study [27], and this may be due to the well-organized biotin SAM. Thus, the above results showed that the SPR sensor chip was prepared successfully.…”
Section: Resultsmentioning
confidence: 63%
“…The reason was that the ureido-and tetrahydrothiophene-rings of biotin are more hydrophilic than −NH 2 terminated cysteamine SAM [26]. The contact angle of biotin SAM was smaller than the previously reported one in study [27], and this may be due to the well-organized biotin SAM. Thus, the above results showed that the SPR sensor chip was prepared successfully.…”
Section: Resultsmentioning
confidence: 63%
“…Pérez-Luna et al 13 showed that SA bound to surface linked biotin via two links at the biotin coverage where steric crowding was observed to initiate on planar surfaces. Consequently on our heterogeneous surface, SA could be assumed to bind to 57% biotin surface-coverage via two links.…”
Section: Manipulating the Sa-biotin Linkmentioning
confidence: 99%
“…It was characterized by Pérez-Luna et al 13 and with more detail by Jung et al 12 that at low biotin surface coverage (<10 %) and high biotin surface coverage (>60 %) SA binds via a single biotin-binding site. Over a median range of biotin surface coverage (10-40 %) mutant streptavidin exhibited second order off rate constants from which they concluded SA binds mainly via two biotin-binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…3C) were 1.49 ± 0.01µM and 260 ± 0.18nM respectively (Fig. 3D) [34,35,36], a configuration demonstrably useful in building up surface structures through accessing the initially unused streptavidin sites pointing away from the surface.…”
Section: Accepted M Manuscriptmentioning
confidence: 97%
“…The increase in tag number results, specifically, in both a higher local concentration of binding points, and a greater receptive surface area at which the large 52.8 kDa streptavidin molecules can be accommodated. The added advantage of streptavidin having four binding pockets increases the potential network of interactions that may occur, though it is likely that only 1-2 binding pockets per streptavidin are bound to any one SQM receptor at any single point in time [34][35][36]. An approximately linear increase in affinity is achieved on adding more tags through the Strep1-Strep5 …”
mentioning
confidence: 99%